BIO-CLIMATIC STRATEGIES FOR SEMI -ARID ZONES: ALIGNING GEOMETRY WITH CLIMATIC FORCES IN WAPDA TOWN AND NFC SOCIETY, LAHORE - Naeem, Shanzae; Gulzar, Rafia; Rashid, Memoona; Kaynat, Ammara (Journal of Arts & Social Sciences, 2025)
The Urban population is increasing densely in Pakistan specially in large cities as people are migrating from Rural to Urban areas for broader life prospects. Lahore has the second highest population and according to research, its population will increase 75% by 2030 due to urbanization (Abbasi, Jabeen, and Khalid 2022).This increased flux of people is imposing load on urban amenities & infrastructure, causing them to be densely populated, more polluted & less sustainable. Primarily responsible for global warming and causing serious health issues, which exacerbate urban heat island (UHI) phenomenon and increase the regional temperature trends (Givoni 1998).In order to escape from this devastating situation, designers need to adopt design considerations which cater to the environment. Bio-climatic approach for urban design & planning can be the solution, where design of urban centers will affect the micro climate of the area to ensure sustainable development as well as energy efficient dwellings. Bio-climatic Urban Design is categorized into Geometric Structure, Vegetation and Construction with different coating materials. In this paper, the aim is to study the effect of aligning urbangeometry with Wind, one of the factors affecting the energy budget of a human being and to generate “Guidelines for bio-climatic urban design for cities in hot, semi-arid climate”. The afore mentioned objective is achieved by the method of critical analysis of literature review. In order to proceed this research, main avenues of two LDA approved society has been taken as a case study to implement the required changes.